The Phyllospadix iwatensis community in the intertidal zone of the Far Eastern seas of Russia - Maria B. Ivanova; Alexandra P. Tsurpalo (Известия ТИНРО)
The community of Phyllospadix iwatensis is studied using materials from expeditions of A.V. Zhirmunsky Institute of Marine Biology (National Scientific Center of Marine Biology, Far Eastern Branch, Russian Academy of Sciences) and archive data (1949-2013) of the Laboratory of Chorology covering the species habitat area from Peter the Great Bay in the south to middle Kuril Islands in the north. The core of the community is identified. It has changing species composition; the changes correspond to geographical boundaries of the cenotic systems of Peter the Great Bay, the Lesser Kuril Islands, and Iturup Island. However, these boundaries do not coincide with the boundaries of the species-edificator habitat that embraces several cenotic systems. Spatial alterations of the cenotic systems are caused by landscape changes conditioned by general geomorphological situation and ecological conditions in the intertidal zone.